A simple but effective design to enhance the performance and durability of direct carbon solid oxide fuel cells. (1st April 2021) - Kong, Wei; Han, Zhen; Lu, Siyu; Ni, Meng
Highlights: The DC-SOFC with an inserted heat bar is proposed. The inserted heat bar promotes the heat transfer in carbon chamber. The average Boudouard reaction rate increases due to the inserted heat bar. The DC-SOFC with heat bar is superior to that without heat bar. Abstract: The development of high-performance and durable direct carbon solid oxide fuel cells requires that the rate of the Boudouard reaction is enhanced without significantly increasing the fuel cell temperature. Herein, a simple design is proposed to improve the performance of direct carbon solid oxide fuel cells by introducing a heat bar into the anode carbon compartment. This design is evaluated numerically using a 2D model. After model validation, parametric simulations are conducted to compare the performance of direct carbon solid oxide fuel cells with and without the heat bar. The heat bar improves the temperature uniformity of the fuel cell and enhances the local temperature in the carbon compartment. As a result, the Boudouard reaction rate is enhanced by 14% at a voltage of 0.6 V, leading to a performance enhancement of 4.1%. The heat bar significantly reduces the difference between the maximum and minimum temperatures in the fuel cell by 40%, leading to improved durability. This design becomes more effective when using a heat bar with a high thermal conductivity and at lower operating voltages. This study clearly demonstrates that this new design is a simple but effective method for enhancing the performance and durability of direct carbon solid oxide fuel cells.